Controlled Release of a Micelle Payload via Sequential Enzymatic and Bioorthogonal Reactions in Living Systems. (29th March 2019) - Porte, Karine; Renoux, Brigitte; Péraudeau, Elodie; Clarhaut, Jonathan; Eddhif, Balkis; Poinot, Pauline; Gravel, Edmond; Doris, Eric; Wijkhuisen, Anne; Audisio, Davide; Papot, Sébastien; Taran, Frédéric
Abstract: A bioorthogonal approach is explored to release the content of nanoparticles on demand. Exploiting our recently described click‐and‐release technology, we developed a new generation of cleavable micelles able to disassemble through a sequential enzymatic and bioorthogonal activation process. Proof‐of‐concept experiments showed that this new approach could be successfully used to deliver the substances encapsulated into micelles in living cells as well as in mice by two complementary targeted strategies. Abstract : Bioorthogonale Nanoexplosion : Nanopartikel mit bioorthogonalen, spaltbaren Iminosydnon‐Linkern lassen sich gezielt zerstören, um ihren Inhalt bei Reaktion mit Cyclooctinen freizusetzen. Dieser Ansatz der kontrollierten Freisetzung wurde erfolgreich in Lebendzellen und Mäusen angewendet.